2021
DOI: 10.34117/bjdv7n12-653
|View full text |Cite
|
Sign up to set email alerts
|

Extenders with vitamins C and E applied to Rhamdia quelen sperm cryopreservation / Extensores com vitaminas C e E aplicados à criopreservação de esperma de Rhamdia quelen

Abstract: We performed this experiment to evaluate the effects of adding vitamins C and E on extenders for sperm cryopreservation of Rhamdia quelen over spermatic mobility after thawing. At cryopreservation, sperm samples were diluted in a proportion of 1:3 (v/v), following pre-freezing in nitrogen steam and subsequent immersion in liquid nitrogen. The diluents were composed by 5% milk powder, 5% glucose, 10% methanol and different levels of vitamin. Three sperm cryopreservation tests were carried out with (1) diluent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…The study results suggested that the supplementation with Vit C, Vit E or their combination positively affected sperm quality (Table 2). Similarly, Xu et al (2015) observed increased sperm motility and viability, indicating improved reproductive performance in turbot (Scophthalmus maximus), rainbow trout (Canyurt and Akhan, 2008), fertilization in Atlantic salmon (Figueroa et al, 2018), and in Rhamdia quelen (Xavier et al, 2021). According to the current results, when given in combination, Vit C and Vit E were likely to synergistically influence hormone synthesis and hormone production, including prostaglandin synthesis.…”
Section: Effects Of Vitamin Supplementation On Reproductive Performancessupporting
confidence: 55%
“…The study results suggested that the supplementation with Vit C, Vit E or their combination positively affected sperm quality (Table 2). Similarly, Xu et al (2015) observed increased sperm motility and viability, indicating improved reproductive performance in turbot (Scophthalmus maximus), rainbow trout (Canyurt and Akhan, 2008), fertilization in Atlantic salmon (Figueroa et al, 2018), and in Rhamdia quelen (Xavier et al, 2021). According to the current results, when given in combination, Vit C and Vit E were likely to synergistically influence hormone synthesis and hormone production, including prostaglandin synthesis.…”
Section: Effects Of Vitamin Supplementation On Reproductive Performancessupporting
confidence: 55%